Exemplar of Liberty Native America and the Evolution of Democracy. Native American Politics Series No. 3 - Grinde, Donald A., Jr.; Johansen, Bruce E. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
Drawing on the historical record and primary sources, this book portrays how Native American political confederacies of the colonial era operated and how their organization and underlying principles influenced the founding fathers of U.S. political institutions. A complementary theme of this book is the intense debate about Native American contributions to the U.S. Constitution and the way in which "established" histories and historical scholars have overlooked the evidence of these contributions. Chapters are arranged along a timeline and cover the following topics: (1) accounts by early English and French traders, missionaries, and settlers about Native political organization and attitudes toward liberty; (2) governance of Native American nations that bordered British colonies; (3) images of Native Americans in European popular culture and the works of major philosophers of the 17th and 18th century; (4) Roger Williams' use of Native precedents for political freedom and religious toleration; (5) ideas of federalism as expressed by Benjamin Franklin and the Iroquois leaders Canassatego and Hendrick (Tiyanoga); (6) images of Native America in popular art, 1763-76, and in the writings of Franklin, Jefferson, and Paine; (7) the Sons of Saint Tammany, a patriotic organization that combined European and Native American ideas and motifs; and (8) references to Native ideas in governance in the 19th and 20th centuries. Contains many references in end-notes, illustrations, and an index. (SV)
Availability: American Indian Studies Center, UCLA, 405 Hilgard Ave., Los Angeles, CA 90024-1548 ($15).
ERIC Note: Foreword by Vine Deloria, Jr.; original artwork by John Kahionhes Fadden. Figures and photographs may not reproduce clearly.
Microfiche.
Keywords: American Indian History; American Indian Studies; American Indians; Constitutional History; Cultural Images; Cultural Interrelationships; Democracy; Governance; Higher Education; Political Influences; Primary Sources; United States History; Iroquois Confederacy; Controversial Topics -- Founding Fathers of the United States -- Historical Distortion -- Native Americans -- United States Constitution; Books; Historical Materials